Seeking Mechanism Improvement of Optimum Prices for New Services in Long-Distance Trains through Use of Nonlinear-in-the-Parameter Analysis Models of Price Elasticity of Demand - S. S. Pastukhov (Вестник Научно-исследовательского института железнодорожного транспорта, 2015)
There is discussed usage pattern of the nonlinear-in-the-parameter economic and mathematical models aimed at increase in efficiency of price elasticity of demand analysis mechanism and search of optimum fees for services of railway passenger transport within the solving framework of profitability management problems. Based on the qualitative characteristics study of the price elasticity of railway passenger traffic demand observables obtained from marketing research as well as on the practice analysis of applying various type mathematical functions to market demand research there were selected five types of nonlinear-in-the-parameter economic and mathematical models for the purpose of examining their potential in the areas of price elasticity of demand analysis and profitability management. Under discussion are methodical approaches to comparative appraisal of application efficiency of various type nonlinear-in-the-parameter economic and mathematical models in the context of price elasticity of demand investigations. Also discussed are application issues of such models in the areas of optimum service fees seeking and profitability management. There was drawn application efficiency comparison of linear and nonlinear-in-the-parameter economic and mathematical models selected for the purpose of price elasticity analysis according to results of their approbation on the marketing data array characterizing services demand in the deluxe and high-speed long-distance trains. On the basis of the obtained results of the economic and mathematical models operation with the marketing information array there were investigated usage pattern and comparative performance of various type application-specific search algorithms of optimum parameters for the selected in the course of the investigation nonlinear model types while engaged in analyzing price elasticity of demand in the light of its specific character in the passenger railway transport environment.